Pengaruh Kemampuan Digital, Orientasi Digital dan Transformasi Digital terhadap Kinerja UMKM di Kota Padang - Subrata, Bimantara; Firman, Firman (Al-DYAS, 2025)
This study aims to analyze the influence of digital capabilities, digital orientation, and digital transformation on the performance of UMKM in Padang City. The results showed that digital capabilities and digital transformation have a significant influence on UMKM performance, while digital orientation did not show a significant effect. Digital capabilities help UMKM optimize business operations and expand market reach, while digital transformation encourages innovation and strengthens competitiveness. In contrast, digital orientation requires more concrete implementation to have a real impact. This study has several limitations, such as limited area coverage in Padang City and a quantitative approach that does not explore the qualitative aspects. The variables studied are also limited to digital capability, digital orientation and digital transformation without considering other external factors. The practical implications of this study include the need for local governments and stakeholders to provide technology training, access to digital infrastructure, and funding to support the digital transformation of UMKM. Academically, the findings can serve as a basis for further studies that highlight other factors that influence UMKM performance, including qualitative approaches to understand the dynamics of digital technology implementation.